DEXAMETHASONE INJECTION INTRATYMPANIC FOR REFRACTORY SUDDEN SENSORINEURAL HEARING LOSS - Lutfullaeva G.U. (Central Asian Journal of Medicine, 2025)
The purpose of this case-control study was to examine the impact of intratympanic dexamethasone injection (ITDI) as a therapeutic alternative for individuals with SSNHL who did not respond to traditional oral steroid therapy. This study comprised sixty-six SSNHL patients who had not responded to an oral steroid treatment regimen. Pure-tone average (PTA) improvement was defined as more than 10 dB. Two (6.1%) of the 33 patients in the control group and 13 (39.4%) of the 33 patients who received ITDI showed improvements in their hearing. Eleven out of twenty patients who did not exhibit any improvement in PTA by ITDI demonstrated improvement over 10 dB in certain frequencies, whereas five out of thirteen patients represented hearing improvement above 20 dB in PTA. There were no definite prognostic factors between the patients who responded to ITDI and those who did not.